IMPLEMENTASI DATA MINING UNTUK MEMPREDIKSI MASA STUDI MAHASISWA MENGGUNAKAN ALGORITMA C4.5 (STUDI KASUS: UNIVERSITAS DEHASEN BENGKULU) - Siska Haryati; Aji Sudarsono; Eko Suryana (UNIVED Press, 2015)
The purpose of this study is to use the C4.5 decision tree algorithm-based and implemented into an application that RapidMiner is expected to improve the accuracy of the analysis of the study period the student. This research was conducted at the Dehasen University of Bengkulu. In the study discussed by monitoring the results of studies at the university in the form of the GPA and the number of credits that have not been accurate for determining a student to graduate on time or not. In this study was to classify the grading of student used data mining techniques with C4.5 algorithms and implemented into Rapid Miner, it aims to see the results of the development can graduate on time or not. From the research results prove that the algorithm C4.5 is more accurate than analysis conducted by analyst’s students. This is evidenced by the results of the evaluation study found C4.5 algorithms capable of analyzing the punctuality of students completing their study.Keyword: Data mining, C4.5 Algorithm